Production of ribbon quenched samples using an arc furnace - Tutzauer, Heriberto A.; Esquinazi, P.; De la Cruz, M. E.; De la Cruz, Francisco (American Institute of Physics, 1980)
Fil: Tutzauer, Heriberto A. Comisión Nacional de Energía Atómica; Argentina